Síntese de catalisadores à base de ouro com diferentes morfologias para a eletrooxidação de glicer - COÊLHO, Anderson Ricardo Pinheiro (2024)
Currently, the search for research on the oxidation of small organic molecules, such as low molecular weight alcohol, has increased significantly. This is due to the fact that these modified molecules are considered potential energy sources with low environmental impact. In this work, the electrooxidation of glycerol on gold nanoparticles of different morphologies, octahedral and dodecahedral, in an alkaline medium was demonstrated. The physical characterization of the material was performed using Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) techniques. The Faradaic processes that occur on the surface of the glassy carbon electrode modified with the material were tested using Cyclic Voltammetry and Chronoamperometry techniques. The data obtained by microscopy demonstrated that the synthesis used in the process actually produced nanoparticles with the desired morphology, i.e., gold dodecahedrons and octahedrons, and that islands and clusters were formed on the surface of the support. The data obtained by cyclic voltammetry with lead (Pb2+) adsorption on its surface allow identifying the presence of the (110) and (111) facets for both of the synthesized materials. Furthermore, the highest values of the catalytic current were found in the gold octahedra when compared to the dodecahedra. However, the potential to initiate glycerol oxidation occurs at lower values in the octahedra. Finally, chronoamperometric measurements in the presence and absence of visible light show differences in the values of the catalytic current at constant potential, indicating that the presence of incident light interferes with the mechanism of alcohol occurrence.